studio del proceso de elaboración del sombrero del pueblo Chibuleo - Paucar Tiche, Karina Lizbeth (2024)
The research focuses on the study of the hat-making process, an artisanal manifestation rooted in the culture of the Chibuleo people. In the Chibuleo people, the hat is characterized by its round crown and a vertical brim, decorated with a blue thread around the crown. This accessory acts as a symbol of identification and distinction between both indigenous and non-indigenous people. This study addresses functional aspects such as the practical usefulness of this emblematic accessory, as well as its cultural meaning rooted in the traditions and identity of this indigenous people. In addition, it focuses on the technical processes linked to the making of the hat worn by the inhabitants of Chibuleo, addressing everything from the careful selection of raw materials to the transformation and finishing techniques. Each step of these processes has been carefully examined, highlighting both its practical or utilitarian relevance, as well as its deep cultural significance. This artisanal practice plays a fundamental role in preserving cultural identity and transmitting traditions to future generations. The study has a qualitative approach, using documentary bibliographic research to build the theoretical framework and field research to explore the processes of making the Chibuleo hat. During the field research, data collection techniques such as semi structured interviews and observation sheets were applied. These tools were essential to encourage the participation of artisans, key informants, and leaders in the research. In summary, the research is distinguished by its balanced and structured approach, aimed at establishing the foundations to generate significant knowledge about the artisanal tradition of Chibuleo hats